Impact of polyphenols on heart failure and cardiac hypertrophy: clinical effects and molecular mechanisms - Hedayati, Neda; Yaghoobi, Alireza; Salami, Marziyeh; Gholinezhad, Yasaman; Aghadavood, Farnaz; Eshraghi, Reza; Aarabi, Mohammad-Hossein; Homayoonfal, Mina; Asemi, Zatollah; Mirzaei, Hamed; Hajijafari, Mohammad; Mafi, Alireza; et al. (Frontiers in Cardiovascular Medicine, 2023)
Polyphenols are abundantly present in regular diets and possess antioxidant, anti-inflammatory, anti-cancer, neuroprotective, and cardioprotective effects. Regarding the inadequacy of the current treatments in preventing cardiac remodeling following cardiovascular diseases, attentions have been focused on improving cardiac function with potential alternatives such as polyphenols. These nutraceuticals are repeatedly indicated to be involved in regulating various heart failure-related vital molecules and signaling pathways, such as inactivation of fibrotic and hypertrophic factors, preventing mitochondrial dysfunction and free radical production as the underlying cause of apoptosis, and improving lipid profile and cellular metabolism. In the current study, we aimed to review the most recent literature and investigations on the underlying mechanism of actions of different polyphenols subclasses in cardiac hypertrophy and heart failure to provide deep insight into novel mechanistic treatments and direct future studies in this context. Moreover, due to polyphenols’ low bioavailability from conventional oral and intravenous administration routes, in this study, we have also investigated the currently accessible nano-drug delivery methods to optimize the treatment outcomes by providing sufficient drug delivery, targeted therapy, and less off-target effects, as desired by precision medicine standards.